2022
DOI: 10.1177/00368504221135469
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with gender and sex differences in anxiety prevalence and comorbidity: A systematic review

Abstract: Background: The prevalence and comorbidity of anxiety disorders are significantly different between women and men, with research showing a greater impact on women. The aim of this review was to identify the psychosocial and biological factors that have been considered to explain this gender and sex difference in prevalence and determine whether these factors are related to any anxiety comorbidity differences between men and women. Methods: Following the PRISMA guidelines, we carried out a systematic review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 108 publications
(266 reference statements)
4
15
1
Order By: Relevance
“…, Bandelow and Michaelis, 2015; Farhane-Medina et al, 2022; Kessler et al, 1994; Kessler et al, 2005b; Pesce et al, 2015; Michael et al, 2007), which is confirmed in our results (for both total group and disorder groups). This sex difference can probably be explained by psychosocial and biological factors, although more research is needed on this (Farhane-Medina et al, 2022). Further, previous studies have primarily documented lower prevalence rates of anxiety disorders in minority groups ( e.g.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…, Bandelow and Michaelis, 2015; Farhane-Medina et al, 2022; Kessler et al, 1994; Kessler et al, 2005b; Pesce et al, 2015; Michael et al, 2007), which is confirmed in our results (for both total group and disorder groups). This sex difference can probably be explained by psychosocial and biological factors, although more research is needed on this (Farhane-Medina et al, 2022). Further, previous studies have primarily documented lower prevalence rates of anxiety disorders in minority groups ( e.g.…”
Section: Discussionsupporting
confidence: 92%
“…For example, anxiety-related disorders are generally more common in women than in men ( e.g. , Bandelow and Michaelis, 2015; Farhane-Medina et al, 2022; Kessler et al, 1994; Kessler et al, 2005b; Pesce et al, 2015; Michael et al, 2007), which is confirmed in our results (for both total group and disorder groups). This sex difference can probably be explained by psychosocial and biological factors, although more research is needed on this (Farhane-Medina et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…It is a normal adaptive response, which may prompt defensive physiological and behavioral changes, but it may become maladaptive or persistent, relating to anxiety and stress-related disorders . Epidemiologic literature consistently suggests that women are at higher risk of anxiety as well as trauma and stress-related disorders and may experience more adverse symptomatic expression of their anxiety compared with men …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence and comorbidity of anxiety disorders are significantly different between women and men, with research showing a greater impact on women. Women experience higher rates of anxious-depressive symptoms compared to men, with these symptoms also being more severe (25)(26)(27). AlJahwari in Oman studied the anxiety symptoms among residents physicians resulting in 251, 68.2% (n = 173) of the study being female residents and 31% (n = 78) male residents (24).…”
Section: Discussionmentioning
confidence: 99%